2015
DOI: 10.1049/iet-map.2014.0130
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly loaded apertures for sub‐diffraction near‐field imaging and surface probing

Abstract: It is demonstrated that electromagnetic (EM) transmission through a subwavelength or non-resonant aperture in a conductive screen can be significantly enhanced by loading it with folded metallic strips exhibiting resonant properties. When illuminated by an EM plane wave, these loaded apertures enable very tight, subwavelength, collimation of the EM power in the near-field zone. The authors propose quasi-planar resonant insertion geometries that should allow, for the first time, simultaneous subwavelength near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The technique was applied for various standoff distances and measurement steps Δx, Δy. It has been observed that in the range of standoff distances λ/25-λ/10 the imaging resolution deteriorates proportionally to z -1.5 where z is an imaging distance [14], [16], [17]. It should be stressed that the measurement step defines the defect resolution and should be of order of the spatial defect deviation [17].…”
Section: Experimental Defect Characterization and Results Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The technique was applied for various standoff distances and measurement steps Δx, Δy. It has been observed that in the range of standoff distances λ/25-λ/10 the imaging resolution deteriorates proportionally to z -1.5 where z is an imaging distance [14], [16], [17]. It should be stressed that the measurement step defines the defect resolution and should be of order of the spatial defect deviation [17].…”
Section: Experimental Defect Characterization and Results Discussionmentioning
confidence: 99%
“…The probe generates a dipole-mode transmitted near field pattern, Fig.2a) with the E-field significantly enhanced in the dipole-mode dual hot spots [14], [16], [17]. The probe supports very high-quality transmission resonance around 4.1GHz, Fig.2b).…”
Section: Imaging Setupmentioning
confidence: 90%
See 3 more Smart Citations